Prediction of strain limits via the Marciniak-Kuczynski model and a novel semi-empirical forming limit diagram model for dual-phase DP600 advanced high strength steel - Kacar, Ilyas (Strojniški vestnik, 2020)
The prediction capability of a forming limiting diagram (FLD) depends on how the yield strength and anisotropy coefficients evolve during the plastic deformation of sheet metals. The FLD predictions are carried out via the Marciniak-Kuczynski (M-K) criterion with anisotropic yield functions for DP600 steel of various thicknesses. Then, a novel semi-empirical FLD criterion is proposed, and prediction capabilities of the criterion are tested with different yield criteria. The results show that the yield functions are very sensitive to anisotropic evolution. Thus, while the FLD curves from the M-K model and the proposed model are not the same for each thickness, the proposed model has better prediction than the M-K model.
Keywords: anisotropy; anizotropija; DP600; forming limit diagram; kriterij porušitve M-K; kriterij tečenja; krivulja mejnih deformacij; M-K failure criterion; yield criterion